Analisis Keterkaitan Inklusi Keuangan Syariah dengan Pembangunan di Negara Anggota OKI - Deni Lubis; Muhammad Giffari Ramadhoni (AL-MUZARA'AH, 2019)
Financial inclusion is one of the main issue on Islamic banking in providing access to financial services to the community. However there are many people who have not access to financial services, especially Islamic banking. This study aims to measure the level of Islamic financial inclusion in several OIC countries (Islamic Cooperation Organization) based on the classification of state income and to analyze the relationship of inclusion of Islamic finance with development. The calculation of the Islamic financial inclusion index used the Index of Syariah Financial Inclusion (ISFI) method. The response variable used in this study is ISFI and the predictor variable is GDP per capita, unemployment rate, number of cellular telephone users, and the population of the village. The method used is descriptive analysis and tobit regression analysis. This study used secondary data from 10 OIC member countries based on the level of state income in 2013-2016. Based on the results of data analysis, high income countries have a high average inclusion rate compared to middle income countries. While GDP per capita and the number of cellular telephone users has a positive effect to the development, meanwhile the unemployment rate has a negative effect.